جهود المنظومة القانونية الجزائرية في مكافحة جريمة الإرهاب في ظل المتغيرات الراهنة -the Efforts Of The Algerian Legal System In Combating The Crime Of Terrorism In Light Of The Current Changes - تازير, آمنة (Université de M'sila, 2019)
المقال تحت عنوان: "جهود المنظومة القانونية الجزائرية في مكافحة جريمة الإرهاب في ظل المتغيرات الراهنة"، حيث أبرزت فيه مفهوم الإرهاب من عدة جوانب، ثم تناولنا خطورة هذه الآفة ولاسيما مع التطور الهائل في أعداد الجماعات الإرهابية والوسائل المستعملة لاستقطاب الضحايا وكذا الحرفية العالية في تنفيذ العمليات الإرهابية، نتيجة لذلك تدخل المشرع الجزائري بترسانة قانونية محاولا بها القضاء على جريمة الإرهاب في الأراضي الجزائرية، خصوصا بعد المجازر التي خلفها الإرهاب في الجزائر خلال العشرية السوداء، هذا ما يثير التساؤل حول نجاعة المنظومة القانونية الوطنية في مجابهة جريمة الإرهاب، وكانت من أبرز التوصيات التي خلصنا إليها هي أنه لابد من تشديد عقوبة الجريمة الإرهابية واعتبارها في أبسط صورها جنايات غير قابلة للتقادم. Abstract Under the title: "Efforts of the Algerian legal system in combating the crime of terrorism in light of the current changes", in which I highlighted the concept of terrorism in many aspects. Then we addressed the seriousness of this scourge, especially with the huge development in the numbers of terrorist groups and means used to attract victims, As a result, the Algerian legislator intervenes with a legal arsenal to try to eliminate the crime of terrorism in the Algerian territories, especially after the massacres left by terrorism in Algeria during the black decade, This raises the question of the effectiveness of the national legal system in dealing with the crime of terrorism. One of the most important recommendations we have reached is that the punishment of terrorist crime must be tightened and considered, in its simplest form, crimes that are not subject to limitation
Keywords: المنظومة القانونية - الإرهاب - الجزائر - المكافحة. ; Legal System - Terrorism - Algeria - Control.